2012
DOI: 10.1177/0333102412452048
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance spectroscopy in migraine: What have we learned so far?

Abstract: Objective: To summarize and evaluate proton (1H) and phosphorus (31P) magnetic resonance spectroscopy (MRS) findings in migraine. Methods: A thorough review of 1H and/or 31P-MRS studies in any form of migraine published up to September 2011. Results: Some findings were consistent in all studies, such as a lack of ictal/interictal brain pH change and a disturbed energy metabolism, the latter of which is reflected in a drop in phosphocreatine content, both in the resting brain and in muscle following exercise. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 73 publications
(551 reference statements)
3
59
0
Order By: Relevance
“…In a retrospective study on patients with subacute daily headache (1-4 weeks durations), we observed that patients with a prior history of febrile illness are more likely to have neck pain and signs of meningismus (in addition to headache). 4 Our observation, 4 Almazov and Brand's observation, 2 and a few other observations 5 suggest a possibility of postinfectious pathology (most likely immunological) in meninges in patients who have a prior history of infections before the onset of headache. We further suggest that the interrelation between meninges and infections may be like the interrelation of synovial membrane to various viral infections for the development of reactive arthritis, as synovial membranes and meninges are of same type of tissue (membranous connective tissue).…”
Section: New Daily Persistent Headache: Disease or Syndrome?mentioning
confidence: 55%
See 1 more Smart Citation
“…In a retrospective study on patients with subacute daily headache (1-4 weeks durations), we observed that patients with a prior history of febrile illness are more likely to have neck pain and signs of meningismus (in addition to headache). 4 Our observation, 4 Almazov and Brand's observation, 2 and a few other observations 5 suggest a possibility of postinfectious pathology (most likely immunological) in meninges in patients who have a prior history of infections before the onset of headache. We further suggest that the interrelation between meninges and infections may be like the interrelation of synovial membrane to various viral infections for the development of reactive arthritis, as synovial membranes and meninges are of same type of tissue (membranous connective tissue).…”
Section: New Daily Persistent Headache: Disease or Syndrome?mentioning
confidence: 55%
“…2 Lakhan et al have selected only 2 studies, both using the 1 H-MRS technique in migraine with aura, and summarize interictal MRS findings in migraine as "a decreased N-acetylaspartate signal and a slight increase in lactate peak" but there is no mentioning of 31 P-MRS data at all. This came as a surprise as:…”
Section: P-mrs In Migraine: Fallen Through the Cracksmentioning
confidence: 99%
“…The hypothesis of the mitochondrial component in migraine neurobiology has been supported in several studies, 32, 33, 34, 35, 36, 37 suggesting that an impairment of the mitochondrial oxidative metabolism, which ultimately causes energy failure in neurons and astrocytes, triggers migraine mechanisms. Furthermore, different types of assays performed in migraine sufferers have shown a decreased activity of the respiratory chain enzymes 33 and a correlation between the extent of the energy disturbance (low ATP levels), and the clinical phenotype severity.…”
Section: Discussionmentioning
confidence: 92%
“…Assays focused on measuring changes in pH have traditionally been performed in humans by collecting plasma, CSF, or using magnetic-resonance spectroscopy or they could also be inferred from other markers e.g. lactate levels [142–144]. But these may not be sensitive enough to detect the small, and potentially local changes in pH that are necessary to activate ASICs.…”
Section: The Future Of Asic-based Therapeutics For Migrainementioning
confidence: 99%